Maternal and cord blood parameters are associated with placental and newborn outcomes in indigenous mothers: A case study in the MINDI cohort (Colombia Medica, 2021)
Background:Multiple infections, nutrient deficiencies and inflammation (MINDI) occur in indigenous communities, but their associations with perinatal outcomes have not been described.Objective:To assess maternal and cord blood micronutrient and inflammation status in peripartum mothers from the Ngäbe-Buglé comarca in Panama, and their associations with placental and infant outcomes.Methods:In 34 mother-newborn dyads, placental weight and diameter were measured, and maternal and cord blood were processed for complete cell counts, serum C-reactive protein, ferritin, serum transferrin receptor (sTfR), vitamins A and D. Blood volumes were calculated using Nadler’s formula.Results:Mothers had low plasma volume (40%, 17.6%) and inflammation (C-reactive protein >8.1 mg/L, 85.3%). Birthweights were normal, but the low placental weight (35.3%), low head circumference Z-scores (17.6%), and low cord hemoglobin (5.9%), iron (79.4%), vitamin A (14.7%) and vitamin D (82.3%) were identified. Maternal and cord vitamin D were highly correlated. Higher maternal plasma volume was associated with heavier placentae (β= 0.57), and higher cord D (β= 0.43) and eosinophils (β= 0.43) with larger placentae. Hemoconcentration (higher cord hematocrit) was associated with lower newborn weight (β= -0.48) and head circumference (β= -0.56). Inflammation [higher maternal neutrophils (β= -0.50), and cord platelets (β= -0.32)] was associated with the lower newborn length and head circumference.Conclusion:Maternal-newborn hemoconcentration, subclinical inflammation and multiple nutrient deficiencies, particularly neonatal vitamin D deficiency, were identified as potential targets for interventions to improve pregnancy outcomes in vulnerable communities.